Infection and co-infection patterns of common upper respiratory tract viruses in patients with flu-like symptoms attending a fever clinic of a tertiary care hospital during the COVID-19 pandemic (Bangabandhu Sheikh Mujib Medical University Journal, 2024)
Background: More than 200 viruses can cause respiratory tract infections. It is clinically indistinguishable to differentiate SARS-CoV-2 viral infections from other viruses that cause flu-like symptoms. This study was done to determine the infection and co-infection patterns of common respiratory tract viruses in patients with flu-like symptoms attending a fever clinic during the COVID-19 pandemic.Methods: A total of 288 participants attending the Fever Clinic of Bangabandhu Sheikh Mujib Medical University having respiratory symptoms were enrolled in this cross-sectional study done from November 2021 to March 2022. Nasopharyngeal swabs were obtained for molecular detection of selected respiratory viruses by multiplex polymerase chain reaction.Results: The study participants were aged 18 to 72 (mean 33.2) years. SARS-CoV-2 infection was 16.7% among the participants, while other respiratory viruses were 24.3% that included rhinovirus (14.6%) followed by adenovirus (5.6%) and parainfluenza viruses (3.5%). SARS CoV-2 and rhinovirus (29.4%), adenovirus and rhinovirus (23.5%), and rhinovirus and parainfluenza virus (17.6%) were the most common co-infections among them (n = 17).Conclusion: Nearly 17% infections were caused by SARS-CoV-2. Rhinovirus infection was the second most common of other  upper respiratory viral infections. There is also evidence of co-infections between SARS-CoV-2 and other common upper respiratory tract viruses.